BUDESONIDE COMPATIBILITY STUDY WITH EXCIPIENTS FOR PREPARATION OF NANOPARTICLE - KUCHEKAR, ASHWIN; JATHAR, JAYESH; GAWADE, ASHWINI (International Journal of Current Pharmaceutical Research, 2021)
Objective: As a condition of acceptance and approval of any pharmaceutical product, stability studies ensuring the durability of the consistency, stability and efficacy of the product during the shelf life are taken into consideration. These studies should be conducted according to the guidelines provided by ICH, WHO and other agencies as intended. Methods: The aim of this research was to evaluate the stability of the budesonide solution in some solutions and excipients and to further study the production of budesonide nanoparticles. In order to study the Budesonide stability mixture of solvent and polymers were used. To study the effect of temperature and relative humidity on the stability of budesonide preparations, prepared mixtures were stored under Accelerated (40 °C±2 °C/75 percent RH±5 percent RH), Intermediate (30 °C±2 °C/65 percent RH±5 percent RH), Long-term (25 °C±2 °C/60 percent RH±5 percent RH) and at 2-8 °C. Results: Budesonide showed good compatibility at defined stability conditions in one month. Such type of preformulation compatibility study is necessary in preparation of nanoparticles. Conclusion: It would be helpful in screening and identifying a suitable solvent, polymer and mixture at a desired concentration.